Associated factors and principal pathophysiological mechanisms of type 2 diabetes mellitus - Wang, Luyao; Li, Lianxin; Liu, Jiaxin; Sheng, Changting; Yang, Maoyi; Hu, Zhipeng; Yue, Rensong (Frontiers in Endocrinology, 2025)
Type 2 diabetes mellitus(T2DM) as a common chronic disease with an increasing prevalence worldwide that poses a great threat to individual health, and is characterized by chronic hyperglycemia resulting from insulin resistance (IR) coupled with β-cell dysfunction. Mitochondrial dysfunction, obesity, gut microbiota, oxidative stress and inflammation have emerged as a significant contributor to the etiology of T2DM, affecting various metabolic processes critical for glucose homeostasis. This short review underscores their role in enhancing T2DM-related molecular mechanisms and explores recent advancements in diabetic management, further highlights the importance of personalized care plans to address the complexities of the T2DM and aims to improve patient quality of life and long-term health outcome.